Dividend Policy and Stock Return: A Study on Some Select Stock in Indian Stock Market (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2019)
Dividend is that portion of profits of a company which is distributable among its shareholders  according to the decision taken and resolution passed in the meeting of Board of Directors.  Dividend policy ploys an important role for maintaining good image of company in the capital  market and in providing source of low cost finance for financing for the profitable future investment  proposals. Objective of the study is to calculate the three measures of (dividend per share, earning  per shore, earning retention ratio) dividend policy of the five selected compa nies Hero Motor  Corporation Limited, Tide water oil company, orocle financial services software limited, lndiabulls  housing finance limited and Vedanta limited and correlate the factors of dividend policy and  return on share price for a period of five years. It was found from the study that only in case of  lndiobulls housing finance limited DPS, EPS, ERR and ROS are positively related. So it can be said  that only in case of lndiabulls housing finance limited company factors of dividend policy are  positively related with ROS.
Keywords: Correlation; dividend per share; earning per share; earning retention ratio